2014
DOI: 10.4137/cpath.s14723
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Teratoma: Case Report and Review of the Literature

Abstract: PURPOSESpinal teratomas comprise a rare subset of spinal cord tumors, and here, we describe an even rarer childhood thoracic extradural–intracanalicular teratoma. The clinical presentation, management, and pathophysiology of these tumors are reviewed to promote recognition and guide treatment of these lesions.METHODSWe report the case of a 21-month-old boy who presented with marked spasticity, as well as failure to ambulate and meet motor milestones. Additionally, we provide a literature review of spinal terat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the differential diagnoses may be: benign bone tumors (such as osteoid osteoma, osteochondroma, giant-cell tumor, aneurysmal bone cyst, and hemangioma), Langerhans cell histiocytosis, and fibrous dysplasia; and malignant tumors, such as sarcomas, teratomas, chordomas, and metastatic lesions. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the differential diagnoses may be: benign bone tumors (such as osteoid osteoma, osteochondroma, giant-cell tumor, aneurysmal bone cyst, and hemangioma), Langerhans cell histiocytosis, and fibrous dysplasia; and malignant tumors, such as sarcomas, teratomas, chordomas, and metastatic lesions. 11…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differential diagnoses may be: benign bone tumors (such as osteoid osteoma, osteochondroma, giant-cell tumor, aneurysmal bone cyst, and hemangioma), Langerhans cell histiocytosis, and fibrous dysplasia; and malignant tumors, such as sarcomas, teratomas, chordomas, and metastatic lesions. 11 For the diagnosis, imaging techniques like CT be used to look for heterogeneous masses, and the MRI, for hypo-or isointense signals in T1-weighted images and hyperintense signals in T2-weighted images. Fluorodeoxyglucose positron emission tomography has not shown good results in the diagnosis and staging of soft-tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature for cases of SET occurring in infants and summarized the characteristics of these cases in Table 1. 1,4,8,[11][12][13]15 We included teratomas inside the spinal canal without intradural extension, but excluded the intraspinal extension of the sacrococcygeal, retroperitoneal, and mediastinal teratomas. Several authors have reported that, with the exception of those originating from the sacrococcygeal region, spinal teratoma is rare.…”
Section: Discussionmentioning
confidence: 99%